STRATEGIES FOR FUTURE DEVELOPMENT OF HUB AIRPORT IN UKRAINE - Akimova, T. A.; Nadutenko, T.V.; Moiseeva, N. O. (Science-based technologies, 2013)
In this article the notion of strategies for future development of hub airport in Ukraine are being investigated. The problem is being considered in terms of potential ways of Ukrainian airports growth which could provide wider network scope at high frequency with cost-effective methods. The estimation of the problem provided a clear view of need in identification of each airport’s functional role in Ukraine as it can show what kind of strategy for the evolution process of the main national airports can be realized; either it is an airport as a hub or an airport with logistics centers. The main goal of this research is to show the advantages and disadvantages of future airport’s development on basis of the national transport system. The intention of the case study was to undertake researches in the field of airport future development which could include creation and extension not only of the permanent but also of the flexible logistics networks simultaneously with carrier-independent system of air transport. According to the analysis, Ukraine has a potential to actualize both strategies.